2017
DOI: 10.1007/s10237-017-0887-5
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic finite element models for brain injury prediction: the sensitivity of axonal strain to white matter tract inter-subject variability

Abstract: Computational models incorporating anisotropic features of brain tissue have become a valuable tool for studying the occurrence of traumatic brain injury. The tissue deformation in the direction of white matter tracts (axonal strain) was repeatedly shown to be an appropriate mechanical parameter to predict injury. However, when assessing the reliability of axonal strain to predict injury in a population, it is important to consider the predictor sensitivity to the biological inter-subject variability of the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 50 publications
0
41
0
Order By: Relevance
“…Meanwhile, Kleiven (2007) used the KTH isotropic FE model to examine the strain in different brain regions, including the midbrain, brainstem, and thalamus, and the relationships between different injury predictors. Later, Giordano et al (2017) used the KTH anisotropic FE model to compare the performance of regional maximum axonal strain (rMAS) against rMPS in different brain regions. Zhao et al (2017) extended Giordano and Kleiven's work using rMAS and sampled across all deep white matter regions of interest and neural tracts to determine regional vulnerabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Kleiven (2007) used the KTH isotropic FE model to examine the strain in different brain regions, including the midbrain, brainstem, and thalamus, and the relationships between different injury predictors. Later, Giordano et al (2017) used the KTH anisotropic FE model to compare the performance of regional maximum axonal strain (rMAS) against rMPS in different brain regions. Zhao et al (2017) extended Giordano and Kleiven's work using rMAS and sampled across all deep white matter regions of interest and neural tracts to determine regional vulnerabilities.…”
Section: Discussionmentioning
confidence: 99%
“…It was not possible to acquire such information based on our historical dataset. However, others have found that when examining how different brains respond to the same loading conditions, the MPS experienced by the brain had a coefficient of variation of 2.33% (Giordano et al, 2017). In our model, we minimized the error introduced by uncertainty in head kinematics by using the most current kinematic loading conditions (Sanchez et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The collection of accelerometer data for FEM analyses has progressed from laboratory‐based impact reconstructions to actual helmeted and unhelmeted impacts from subject data (McAllister et al, ; Patton, McIntosh, & Kleiven, ; Viano et al, ; Zhang, Yang, & King, ). Additionally, recent research incorporated WM anisotropy from DTI scans into the FEM (Giordano, Zappalà, & Kleiven, ). Collectively, these studies agree that peak strains and stresses of concussive injury are located near the brainstem in central brain areas such as the midbrain, thalamus, and corpus callosum regardless of the actual head impact location.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 illustrates the white matter fiber tracks in the brain of a healthy subject. The physics and mechanics of axonal fiber tracts is important in various fields including understanding axonal injury [5], [6], predicting the source of electrical signals [7], [8], and learning about brain structure-function relationships [9]- [11]. Recently, we have been using the embedded element approach to understand and predict axonal injury due to impact or blast loading to the head [12]- [15].…”
Section: Introductionmentioning
confidence: 99%